Hyperinflation, kollektives Gedächtnis und Zentralbankunabhängigkeit - Ulrike Neyer; Daniel Stempel (Wirtschaftsdienst, 2023)
– The German hyperinflation in 1923 was caused by monetary financing of the highly deficient German state budget by a de-pendent central bank. The social and economic consequences of the hyperinflation were disastrous. Combined with an instable politi-cal atmosphere, paving the way for the rise of the Nazis, the hyperinflation is deeply etched in the German collective memory. It is this collective memory that shapes the current institutional framework of the ECB. While risk aversion and institutional imprint of the ECB'S policy makers differ, the ECB's institutional framework ensures that current inflation will not evolve into a hyperinflation.
Keywords: E31; E42; E58; 330; Hyperinflation; Zentralbank; Wirtschaftsgeschichte; Deutschland (bis 1945); Deutschland